Influence of School and Students Factors on Mathematics Achievement - Mahmood, Sadia; Khatoon, Tahira (INDIAN EDUCATIONAL REVIEW, 2011)
This study examined the effects of school type, gender and mathematics anxiety on mathematics achievement. The population consists of 863 males and 789 females from 15 secondary schools of Uttar Pradesh (India). The Mathematics Achievement Test and Mathematics Anxiety Scale were used for data collection, while stepwise multiple regression, ANOVA, t-test and correlation techniques were used for statistical analysis. The results of the analysis showed that among the three independent variables, school type had the greatest influence on mathematics achievement (46%), mathematics anxiety comes second in order while gender showed no significant influence. Moreover, the students of Missionary and A.M.U. schools had highest mathematics achievement, while students of Government and Government Aided schools had lowest achievement scores, moreover scores of students of Muslim and Hindu Managed schools slide in between the range of highest and lowest achievement. Further males reported more mathematics achievement than females and students with low mathematics anxiety had highest achievement scores. Findings also reveal a significant negative correlation (–0.48) between mathematics achievement and mathematics anxiety.